Gambaran Prevalensi Hasil Pemeriksaan IMLTD di UTD Kabupaten Banjar Tahun 2022-2023 - Nurmilawati Nurmilawati; Devina Yolanda; Mailisa Irhamna; Sheila Nurrahmah; Muhammad Irfan; Thoriq Ahmad Huwaidi (Jurnal Kesehatan Indonesia, 2025)
Blood transfusion is a vital health service that saves lives but carries the risk of transfusion transmissible infections (TTIs), highlighting the need for rigorous donor screening. This study aimed to assess the prevalence of TTIs among blood donors at the Indonesian Red Cross (PMI) Blood Transfusion Unit, Banjar Regency, in 2022–2023. A descriptive retrospective cross-sectional design was applied using secondary donor data with total sampling. Variables included HIV, hepatitis B, and syphilis, analyzed using univariate methods. Most donors were male (80.83%), aged 25–44 years (55.12%), with blood group O dominant (37.40%), and the majority were regular donors (55.01%). In 2022, of 6,154 samples, 71 (1.15%) were reactive: HBsAg 77.46%, syphilis 18.31%, and HIV 4.23%. In 2023, of 6,538 samples, 72 (1.10%) were reactive: HBsAg 63.89%, syphilis 26.39%, and HIV 9.72%. Overall, the prevalence of reactive samples remained stable, with hepatitis B as the most common infection, though its proportion decreased, while syphilis and HIV showed increases. These findings highlight the importance of strengthening donor screening, expanding prevention programs, and improving public education to ensure safe and reliable blood supplies.